Inovasi Produk Dan Pengembangan Label Halal Dalam Meningkatkan Daya Saing Ekonomi Syariah - Bayu Priyadi; Muhammad Danil Sultara; Eka Afrialia Putri; Valina Dewi Sekar M; Junita Sari; Aulia Intan Zahra; Muhammad Arifudin; Havid Jibril (CV. Doki Course and Training, 2025)
The Islamic economy, as a vital pillar of Indonesia's economic landscape, continues to grow alongside increasing consumer awareness of halal products. Product innovation and the development of halal certification labels are strategic keys to enhancing the competitiveness of Islamic economy products in both domestic and global markets. This article discusses how halal product innovation, integrating technology and quality standards, along with strengthening halal certification and labeling, can expand market share, boost consumer trust, and drive sustainable growth in the Islamic economy. The study employs a literature review of various research and reports. The findings indicate that halal product innovation combined with the development of halal labels plays a significant role in improving business competitiveness, expanding market access, and supporting sustainable growth of the Islamic economy. ABSTRAK Ekonomi syariah sebagai salah satu pilar penting dalam perekonomian Indonesia terus berkembang seiring dengan meningkatnya kesadaran konsumen terhadap produk halal. Inovasi produk dan pengembangan label halal menjadi kunci strategis dalam meningkatkan daya saing produk syariah di pasar domestik maupun global. Artikel ini membahas bagaimana inovasi produk halal yang mengintegrasikan teknologi dan standar kualitas serta penguatan sertifikasi dan label halal dapat memperluas pangsa pasar, meningkatkan kepercayaan konsumen, dan mendorong pertumbuhan ekonomi syariah. Metode kajian menggunakan telaah literatur dari berbagai penelitian dan laporan terkait. Hasilnya menunjukkan bahwa inovasi produk halal yang disertai pengembangan label halal berperan signifikan dalam meningkatkan daya saing usaha, memperluas akses pasar, dan mendukung pertumbuhan ekonomi syariah secara berkelanjutan.